Ablation of adipocyte creatine transport impairs thermogenesis and causes diet-induced obesity. Issue 3 (25th February 2019) - Kazak, Lawrence; F.Rahbani, Janane; Samborska, Bozena; Lu, Gina Z.; Jedrychowski, Mark P.; Lajoie, Mathieu
No abstract available